2015
DOI: 10.1016/j.surfcoat.2015.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Industrial-scale high power impulse magnetron sputtering of yttria-stabilized zirconia on porous NiO/YSZ fuel cell anodes

Abstract: Yttria-stabilized zirconia (YSZ) thin films are reactively sputter-deposited by high power impulse magnetron sputtering (HiPIMS) in an industrial setup on porous NiO/YSZ fuel cell anodes. The influence of deposition pressure, peak power and substrate bias on the deposition rate and film morphology is studied. It is seen that depositing at increasing the deposition pressure from ~370 mPa to ~750 mPa results in a 64 % increase in the deposition rate and denser film. Films are deposited at peak power densities ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Great efforts have been made to apply reactive magnetron sputtering to build gastight, thin electrolytes on the anode support . Fabrication of gastight thin film electrolytes on porous anode supports is not an easy task because the surface of the anode support usually contains pores with diameters in the range of several micrometers, which leads to pinholes formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Great efforts have been made to apply reactive magnetron sputtering to build gastight, thin electrolytes on the anode support . Fabrication of gastight thin film electrolytes on porous anode supports is not an easy task because the surface of the anode support usually contains pores with diameters in the range of several micrometers, which leads to pinholes formation.…”
Section: Introductionmentioning
confidence: 99%
“…This cell's size is obviously insufficient for the manufacture and testing of SOFS stacks. Sønderby et al demonstrated deposition of YSZ thin films by high power impulse magnetron sputtering in an industrial setup on 13 × 13 cm 2 porous NiO/YSZ fuel cell anodes. However, a whole fuel cell in this work was not produced and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Most often to deposit YSZ electrolyte, sputtering in DC-pulsed mode is used. However, in the works of Sonderby et al [37,38], for depositing the YSZ electrolyte on NiO/YSZ anodes, high power impulse magnetron sputtering was used. HiPIMS utilizes extremely high power densities of the order of kW/cm 2 in short pulses of tens of microseconds at low duty cycle (on/off time ratio) of <10%.…”
Section: Magnetron Sputtering Of Ysz Electrolyte Effect Of Depositiomentioning
confidence: 99%
“…In their next paper, Sonderby and co-authors [38] optimized the parameters of high power reactive magnetron sputtering and the magnitude of the bias voltage. As a result, YSZ electrolytes up to 3 µm thick are deposited on the anodes with an area of (13 × 13) cm 2 .…”
Section: Magnetron Sputtering Of Ysz Electrolyte Effect Of Depositiomentioning
confidence: 99%
“…The tetragonal phase is the most commonly used phase and can be stabilized at STP by alloying with different early transition metal oxides, the most common being Y2O3 [58,59]. The cubic fluoride phase is used as electrolyte in solid-oxide fuel cells due to its high ionic conductance [60,61].…”
Section: Zro2 Polymorphsmentioning
confidence: 99%